Fourier transform-infrared microspectroscopy and microscopic imaging - Gourion-Arsiquaud, Samuel; West, Paul A; Boskey, Adele L (Methods in molecular biology (Clifton, N.J.), 2008)
For age- and sex-matched subjects, osteoporotic bone is more fragile than healthy bone. Vibrational infrared spectroscopy and in particular infrared microspectroscopic imaging is a useful tool for investigating and characterizing changes associated with metabolic bone diseases including osteoporosis in biopsied tissues. Strength-related measures such as bone mineral content/composition as well as spectroscopically determined bone quality-related measures such as mineral crystallinity, carbonate substitution, and collagen cross-linking consequently differ between osteoporotic patients and normal subjects. Validated IR parameters specific to the mineral and matrix components of bone have been defined and can now be used to quantify anatomical/spatial variations and the effect of new therapies on osteoporotic bone.